Pelaksnaan Hak Asasi Manusia (HAM) di Dalam Birokrasi Pada Kasus Pembebasan Tanah - Agus Heruanto Hadna (Magister Administrasi Publik, 1998)
This research has an anxiety of a lot of human right delinquency cases. Some of those delinquents are bureacrats. Therefore, the research question is why bureaucracy commits to human right violations especially in land law-suit cases? Is there any condition that stimulates those violations? And what type of bureacrats who have high or low appreciation for human right? The research takes land law-suit cases because it is one of the biggest human right cases in Indonesia. Theoretically, bureaucrat commits to human right violation because they have bad attitude that is influenced by patrimonialism culture or profit oriented behavior for personal interests. Meanwhile, the structure of bureaucracy that are hierarchical and rigid stimulates bureaucrats to be more responsive to superior than community. The research has found that there are four conditions making bureaucrats ignore human right value. Those conditions are: emphasis on economic growth, lack of human resources capacity, profit takers, and ambiguity of land constitutions. The research has also found four types of bureaucrats who are categorized based on bureaucrats orientations to development and constitutions. They are: an adventurer type, a bureacrat who commits to human right violation on either political, economic, and culture aspects; an authocratic type, a bureaucrat who commits to human right violation on political and economic aspects; an developer type, a bureaucrat who commits to human right violation on political aspects; and, a humane type, a bureaucrat who gives high appreciation for human right values.